Efeitos de campos magnéticos intensos sobre as propriedades opto-eletrônicas de poços quânticos assimétricos - Ademir Ricart Alves (1998)
We study the magnetic field effects, up to 15 T, on the two-dimensional electron gas confined in an asymmetric quantum well of n - AlxGa1-xAs / InyGa1-yAs / GazAs1-z grown by Molecular Beam Epitaxy. With the magnetic field applied parallel to the interfaces of the quantum well, planar magnetic field, we study the effect of depopulation of the electronic subbands of the system. Using a custom designed sample, in which the second electronic subband is slightly populated, we show for the first time that the effect of depopulation caused by the planar magnetic field can be studied optically. We find that, as the magnetic field intensity is increased, the change in the magnetoresistance of the sample agrees very closely to the change in the intensity of the photoluminescence (PL) line associated with recombination from the second electronic subband of the system. By means of a numeric self-consistent calculation we show that the depopulation induced by the planar magnetic field exhibits a behavior qualitatively identical to that observed in the optical and electrical measurements. With the magnetic field applied perpendicular to the interfaces of the well, we study the origin of the magneto-optical oscillations in the PL intensities of the recombinations associated with the first (e1) and the second (e2) subbands. The 180o phase difference between them was attributed to the limited number of photo-excited holes. For the first time, we show that the extremes of these oscillations occur for the same B-values in which a resonant polaron is formed (LO). At these B-fields the intensities of the PL lines originating from the Landau levels of e2 with the simultaneous emission of an longitudinal optical (LO) phonon are strongly enhanced. This suggests that the minima in the oscillations are due to an increase in the LO phonon scattering of the electrons near the Fermi level. This interpretation is confirmed by the variation with magnetic field of the width of the PL line arising from recombination of the e2 electrons. We find that in the polaron resonance conditions the PL linewidth associated with recombination from the e2 fundamental level goes through a maximum, thus showing that in the resonance conditions the electrons in this energy level are strongly scattered.